HIV-INFECTED PREGNANT WOMEN ATTENDING REFERENCE SERVICE: CLINICAL AND SOCIODEMOGRAPHIC FEATURES - Pimenta, Ana Teresa Mancini; Duarte, Geraldo; Couto-Fernandez, José Carlos; Correa, Isadora Alonso; Melli, Patricia Pereira dos Santos; Quintana, Silvana Maria (Journal of Health Care, 2015)
Introduction: It is important to identify features of HIV-infected pregnant women, to develop actionsto improve assistance for these women. Objective: The purpose of this study was to describe pregnantwomen infected with human immunodeficiency virus (HIV), attended at outpatient clinic of infectiousdisease in obstetrics in Ribeirão Preto (SP). Materials and methods: It was performed a cross-sectionalstudy during the period 2010-2012, using secondary data from medical records. Results: It were included113 pregnant women with HIV infection with an average age of 28.9 years, most of them were white(62.8%), married or cohabitating (71.7%), and formal education of 31.9% were between 9 and 11 years.Was observed that diagnosis of HIV infection of most women occurred during prenatal exams, late onsetof prenatal care, and majority were asymptomatic. The most frequent complication during pregnancy wasanemia. Good adherence to antiretroviral therapy was observed for 60.0% of pregnant women. While58.7% of them presented undetectable viral load around the 34th week of gestation, 29.8% presented viralload above 1,000 copies/mL. Delivery of 82.5% of women was carried out with a gestational age over 37weeks; the mode of delivery of 51.0% was cesarean section. Conclusions: The results show predominanceof HIV-infected pregnant women in the age group 25-34 years old; most were asymptomatic and haddiagnosis of HIV infection due to antenatal tests.